2022
DOI: 10.22219/jpbi.v8i1.16917
|View full text |Cite
|
Sign up to set email alerts
|

Developing Madura local content and augmented reality-based digital textbook to improve scientific reasoning ability

Abstract: Textbooks currently circulating have not been adapted to online learning systems and their contents are less interactive, less communicative, and have not been based on local content potential. This research aimed to produce digital textbooks based on Madura local content and augmented reality to improve students’ scientific reasoning ability. This research development was done based on ASSURE instructional design, between July and August 2020. This research involved 15 students of SMP Al-Hikam Burneh, Bangkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This is in line with research which shows that the use of comics and story-reading books can increase elementary school students' reading literacy, especially if presented with local wisdom values so that they can teach character values in elementary schools (Murti et al, 2020;Wahab & Amaliyah, 2021). In addition, so that students are interested in reading textbooks, an innovation is needed to improve participants' reading skills by adopting digital-based books augmented reality or picture textbooks (Mcgeown et al, 2016;Yasir et al, 2022). This is in line with research showing that augmented reality as a medium used to collaborate digital book-based reading materials can foster students' interest in reading because it is made according to the development of elementary school students (Meletiou-Mavrotheris et al, 2020;Sari et al, 2022).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is in line with research which shows that the use of comics and story-reading books can increase elementary school students' reading literacy, especially if presented with local wisdom values so that they can teach character values in elementary schools (Murti et al, 2020;Wahab & Amaliyah, 2021). In addition, so that students are interested in reading textbooks, an innovation is needed to improve participants' reading skills by adopting digital-based books augmented reality or picture textbooks (Mcgeown et al, 2016;Yasir et al, 2022). This is in line with research showing that augmented reality as a medium used to collaborate digital book-based reading materials can foster students' interest in reading because it is made according to the development of elementary school students (Meletiou-Mavrotheris et al, 2020;Sari et al, 2022).…”
Section: Discussionsupporting
confidence: 80%
“…Based on the Table 2, 15 articles identified the use of the literacy movement as an effort to develop literacy skills in elementary schools. Specifically, 5 literacy movements can be used as an effort to build literacy skills in elementary schools, namely literacy culture strategies (Hyman et al, 2020;Imran et al, 2011;Liansari et al, 2021;Marmoah & Poerwanti, Suharno, 2022;Nuangchalerm & Intasena, 2022;Su & Ma, 2021), use of digital technology (Izhar et al, 2022;Mumpuni et al, 2021;Murti et al, 2020), procurement of reading books (Senen et al, 2021;Sri et al, 2021;Yasir et al, 2022), development of library facilities and character building (Farikah, 2019;Subur et al, 2022), take part in a national assessment (Hendrowati & Faelasofi, 2021). The number of research articles found in software Publish or Perish 8 with systematic objectives can be detailed in the Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation